Evaluation of the Opinions and Knowledge of Medical School Students on Organ Donation and Transplantation - Kaygusuz, Turkkan Ozturk; Pirincci, Edibe (Aves, 2021)
Background: Insufficient organ donation is one of the most significant current problems in medical care. The students of the faculty of medicine could be the strongest supporters of organ donation and transplantation, and may play an important role in increasing organ donation. This study aimed to determine the relevant educational needs of the medical students by evaluating their knowledge and opinions about organ donation and transplantation, according to their grade levels. Methods: A cross-sectional study was conducted among 395 (83.6%) students in the first, third, and sixth grades of the faculty of medicine. A questionnaire consisting of 42 questions was used to measure their opinions and knowledge about organ transplantation. Results: Among the students who responded, 6.8% (n = 27) had donated their organs and 81.4% of the donors had donation cards, while 73.4% (n = 290) were considering organ donation. The percentages of women and students at the grade six level considering organ donation were significantly higher (P <.05). The study revealed that 38.7% of the students did not have enough knowledge about organ donation, 47.8% stated that they hod some knowledge and 61.8% of the students did not know the principles of brain death. The students of all grades reported that most of the information about organ donation and transplantation was obtained from their family and friends. Conclusion: As medical students progress through the grade levels, their perceptions and knowledge of organ donation and transplantation also increase positively. Courses on organ donation and transplantation can be added to the curriculum from the very first year of medical education.
Keywords: Organ donation; transplantation; education; medical students; opinions